Precipitation behavior and mechanical properties of a hot-worked TiNbTa0.5ZrAl0.5 refractory high entropy alloy. (January 2020) - Cao, Yuankui; Liu, Yong; Li, Yunping; Liu, Bin; Fu, Ao; Nie, Yan
Abstract: A TiNbTa0.5 ZrAl0.5 refractory high entropy alloy was prepared by powder metallurgy and subsequently subjected to hot forging. The precipitation behavior and its effects on compression properties were studied. Results show that the as-sintered TiNbTa0.5 ZrAl0.5 alloy has a single BCC phase. The primary BCC phase is thermodynamically instable, and decomposes into BCC (Ti, Nb, Ta)-rich matrix and HCP (Zr, Al)-rich precipitates after hot forging. The precipitates are much harder than the matrix, and have significant strengthening effect. The hot-worked TiNbTa0.5 ZrAl0.5 alloy has a high compressive yield strength of 1740 MPa with a considerable compressive ductility of 12% at room temperature. The precipitation strengthening contributes about 51% while the grain-boundary strengthening contributes 35% to the increment of the yield strength. Highlights: The powder metallurgy TiNbTa0.5 ZrAl0.5 alloy has a single BCC phase structure. Hot forging leads to a formation of HCP precipitates in the primary BCC matrix. The alloy has a compressive yield strength of 1740 MPa with a plasticity of 12%. Precipitation strengthening contributes most to the increment of yield strength.